Predictive immunohistochemical features for tumour response to chemoradiotherapy in rectal cancer. Issue 2 (5th February 2020) - Shinto, E; Omata, J; Sikina, A; Sekizawa, A; Kajiwara, Y; Hayashi, K; Hashiguchi, Y; Hase, K; Ueno, H
Abstract: Background: Reduced expression of cluster of differentiation (CD) 133 and cyclo-oxygenase (COX) 2, and increased density of CD8+ tumour-infiltrating lymphocytes, are associated with a favourable tumour response to preoperative chemoradiotherapy (CRT). This study aimed to evaluate these markers in relation to tumour response after preoperative CRT in two rectal cancer cohorts. Methods: Patients with low rectal cancer who underwent radical resection and preoperative short-term CRT in 2001–2007 (retrospective cohort) and long-term CRT in 2011–2017 (prospective cohort) were analysed. Pretreatment biopsies were stained immunohistochemically using antibodies to determine CD133 and COX-2 expression, and increased CD8+ density. Outcome measures were tumour regression grade (TRG), tumour downstaging and survival. Results: For 95 patients in the retrospective cohort, the incidence of TRG 3–4 was 67 per cent when two or three immunohistochemistry (IHC) features were present, but only 20 per cent when there were fewer features ( P < 0·001). The incidence of tumour downstaging was higher in patients with at least two IHC features (43 versus 22 per cent with fewer features; P = 0·029). The 49 patients in the prospective cohort had similar rates to those in the retrospective cohort (TRG 3–4: 76 per cent for two or more IHC features versus 25 per cent with fewer features, P < 0·001; tumour downstaging: 57 versus 25 per cent respectively, P = 0·022). Local recurrence-free survival rates in patients with more or fewer IHC features were similar in the retrospective and prospective cohort ( P = 0·058 and P = 0·387 respectively). Conclusion: Assessment of CD133, COX-2 and CD8 could be useful in predicting a good response to preoperative CRT in patients with lower rectal cancer undergoing neoadjuvant therapy. Further studies are needed to validate the results in larger cohorts and investigate a survival benefit. Graphical Abstract: The combination of reduced expression of cluster of differentiation (CD) 133 and cyclo-oxygenase (COX) 2 and increased density of CD8+ tumour-infiltrating lymphocytes is a significant predictor of tumour response to preoperative chemoradiotherapy (CRT). This finding may be clinically useful for determining chemoradiosensitive cancers. Immunoistochemistry features of tumor regression in rectal cancer